Industrial wastewater treatment : removal of ammonia-nitrogen and orthophosphate in palm oil mill effluent using constructed wetland - Siti Nurbaya, Mustafa Kamal (2009)
Wastewaters from industrial places are very complex and lead to water pollution if discharged untreated, especially due to its high organic loading. Palm oil mill effluent (POME) is a brownish liquid that contain high amount of nitrogen and phosphorus that has been produced from the palm oil processing plants. Therefore, wastewater treatment such as constructed wetland is needed to decrease the effect of contamination. Constructed wetland is a wetland that specifically constructed for pollution and waste management. The objective of this research is to study the efficiency of constructed wetland to treat pollutant in POME. Parameters concerns are ammonia-nitrogen (NH3-N) and orthophosphate (PO43-). In this study, lab scale of free water surface had been constructed by using water lettuce (Pistia stratiotes) as wetland plant and gravel as filter. This experiment consists of two systems which are without and with cycle. Each system was conducted on four stages; first and third stage used gravel as a filter whereas second and fourth stage used constructed wetland to remove the pollutant. This experiment was conducted with different concentrations of sample which are 100% concentration and 80% concentration. For the first system (without cycle)which is 10 days of treatment, 93.36% of NH3-N and 79.54% of PO43- had been removed from 100% sample concentration while 90.95% of NH3-N and 78.52% of PO43- removed from 80% of sample concentration. For the second system (with cycle) which is 20 days of treatment, the optimum days of treatment was 15 days which give the optimum results of 98.39% of NH3-N and 83.12% of PO43- from 100% sample concentration whereas 96.37% of NH3-N and 80% of PO43- removed from 80% sample concentration. From the results, they show that the percent removal of NH3-N is much higher than PO43-. As a conclusion, constructed wetland can be used as industrial waste treatment and also gives high efficiency in removal of contaminant in POME.